2016
DOI: 10.1115/1.4033363
|View full text |Cite
|
Sign up to set email alerts
|

Dry Sliding Wear Behavior of Ti-6Al-4V Pin Against SS316L Disk at Constant Contact Pressure

Abstract: Ti-6Al-4V pins were slid against SS316L disks in pin-on-disk arrangement using pins of different diameters; with the contact pressure maintained the same for all experiments under ambient and vacuum conditions. Characterization of the tribological samples was performed using scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX), and X-ray diffraction (XRD). The tribological behavior was found to be governed by strain rate response (SRR), tribo-oxidation (TO), formation of a mechanically m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Abrasive lines found on the wear tracks of all the printed/heat treated specimens are attributed to abrasive wear that results from the repeated sliding of the 100Cr6 steel balls [6,12,18,19] , c and d) have an additional O peak, which is not detectable on the untested area (Fig. 6a), as a result of a dry-slidinginduced oxidation process [12,14,[20][21][22]. In Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abrasive lines found on the wear tracks of all the printed/heat treated specimens are attributed to abrasive wear that results from the repeated sliding of the 100Cr6 steel balls [6,12,18,19] , c and d) have an additional O peak, which is not detectable on the untested area (Fig. 6a), as a result of a dry-slidinginduced oxidation process [12,14,[20][21][22]. In Figs.…”
Section: Resultsmentioning
confidence: 99%
“…5f.The EDX spectra of the printed Ti6Al4V specimens shown in Figs.6a-dare mainly composed of Ti, Al, and V peaks[6,10,12]. The EDX spectra detected on the wear tracks (Figs.6b, c and d) have an additional O peak, which is not detectable on the untested area (Fig.6a), as a result of a dry-slidinginduced oxidation process[12,14,[20][21][22].…”
mentioning
confidence: 99%
“…Moreover, the size of the pin also plays a significant role in controlling the particulates, as for larger pins (size > d/∅ = 0.004 m) the area of contact is higher. Therefore, it can aid in achieving a prolonged retention time for the particulates [21].…”
Section: Basis Of Analysismentioning
confidence: 99%
“…Hence, the subsurface zones will undergo plastic deformation and the abrasive debris particles (generally hard in nature) will favor micro-cutting and ploughing, leading to the formation of furrows and grooves [Figure 6(a)]. Raj et al (2017) suggested that the BTi64 alloy demonstrates the lowest wear behavior at a sliding speed of 0.5 ms À1 because of the formation of surface oxides (especially TiO). However, with further increment in sliding speed (above 0.5 ms À1 , inclusive of 0.838 ms À1 as in the present case), the MML formed becomes highly unstable.…”
Section: Evaluation Of the Existence And Evolution Of Surface Compoundsmentioning
confidence: 99%
“…Among them, the Ti6Al4V (Ti64, a-b alloy, Grade V) with its unique features gradually became the immensely used material. Nonetheless, the indigenously poor tribological characteristics of the alloy delimit its applicability in mechanisms involving surface to counter-body interactions (Raj et al, 2017). Although so, the material has received superior consideration for implementation in applications requiring high dynamic wear resistance (Blau et al, 2007).…”
Section: Introductionmentioning
confidence: 99%